2012
DOI: 10.1038/cgt.2012.76
|View full text |Cite
|
Sign up to set email alerts
|

Increased invasion of malignant gliomas after 15-LO-1 and HSV-tk/ganciclovir combination gene therapy

Abstract: Recent clinical trials for malignant glioma have drawn attention to the potential therapeutic efficacy of herpes simplex virusthymidine kinase (HSV-tk) suicide gene therapy. Nevertheless, because of the nature of these tumors, it is believed that no single treatment alone is able to combat this fatal disease. Combination therapies may provide a solution to further improve therapies against malignant gliomas. We have recently demonstrated that 15-lipoxygenase-1 (15-LO-1) is able to inhibit tumor angiogenesis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Therapeutic delivery of a lipoxygenase in a therapeutic context is a new approach. In recent studies, gene transfer of lipoxygenase 15-1 was used for inhibition of angiogenesis in different setting [ 27 , 28 ]. We expect that genetic transfer of AmbLOXe as an inducer of cellular growth is an important option for future therapeutic approaches, especially in the context of nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic delivery of a lipoxygenase in a therapeutic context is a new approach. In recent studies, gene transfer of lipoxygenase 15-1 was used for inhibition of angiogenesis in different setting [ 27 , 28 ]. We expect that genetic transfer of AmbLOXe as an inducer of cellular growth is an important option for future therapeutic approaches, especially in the context of nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome this problem, scientists have created certain vectors such as engineered adenoviral vectors and cationic liposomes (14,15). However, some vectors are not able to be expressed in various types of human cancer (31). In the present study, the pAV-murine cytomegalovirus-GFP-3FLAG vector was used to transport the therapeutic genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the pAV-murine cytomegalovirus-GFP-3FLAG vector was used to transport the therapeutic genes. A previous study indicated that NIS expression is primarily controlled by the thyroid-selective transcription factors paired box gene 8 (Pax-8) and NK2 homeobox 1 (Nkx2.1) in thyroid cancer (31). Pax-8 and Nkx2.1 target the NIS upstream enhancer through the cardiac homeobox transcription factor Nkx2 (16,32).…”
Section: Discussionmentioning
confidence: 99%
“…HSV vectors have been developed for human gene therapy of brain tumors, such as glioblastoma multiforme, and for conditions such as chronic pain (37)(38)(39)(40)(41)(42)(43)(44). The greatest number of trials have been done for malignant brain tumors, where HSV vectors have been used to deliver prodrug-activating enzymes, resulting in so-called "suicide gene" therapy and in some cases resulting in the release of tumor-specific antigens at a locus at which inflammation was triggered by the viral components of the vector (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Herpesvirus Vectorsmentioning
confidence: 99%